Structural features of polysaccharides from Physalis pubescens L. stem, and their neuroprotective effects and anti-aging activities. - Zhou, K.; Zhang, X.; Liu, X.; Li, D.; Gao, P. (International Journal of Biological Macromolecules, 2025)
To identify and evaluate potential functional adjuvants from Physalis pubescens L. stem, two novel acidic polysaccharides (PPLS-1 and PPLS-2) were isolated from this economic crop using deproteinisation, depigmentation and purification with DEAE-52 and Sephadex G-200 column chromatography. Structural characterization revealed that PPLS-1 and PPLS-2 have molecular weights of 12.7 kDa and 11.6 kDa, respectively. Monosaccharide composition analysis indicated that both polysaccharides consist of Rha, Ara, Man and Gal. Nuclear magnetic resonance (NMR) spectroscopy further demonstrated that PPLS-1 contains ?2)-?-D-Rhap-(1?, ?5)-?-L-Araf-(1?, ?4)-?-D-Manp-(1?, and ?-D-Galp, whereas PPLS-2 comprises ?4)-?-D-Galp(1?, ?5)-?-L-Araf(1?, ?2,4)-?-L-Rhap(1? and ?4)-?-D-Manp(1?. The antioxidant activities of PPLS-1 and PPLS-2 were evaluated, revealing significant scavenging capabilities against 1,1-diphenyl-2-picrylhydrazyl (DPPH) and 2,2'-azino-bis-(3-ethylbenzthiaz oline-6-sulphonic acid) (ABTS). Moreover, treatment with these polysaccharides effectively protected SH-SY5Y cells from hydrogen peroxide-induced damage, indicating pronounced neuroprotective effects. PPLS-1 exhibited antioxidant properties by reducing malondialdehyde (MDA) levels and enhancing the activities of superoxide dismutase (SOD), total antioxidant capacity (T-AOC) and glutathione peroxidase (GSH-Px). Western blot analysis confirmed that PPLS-1 significantly decreased Keap1 protein expression and increased Nrf2 and HO-1 protein expression, suggesting its role in modulating the Keap1-Nrf2/HO-1 signalling pathway to alleviate H2O2-induced oxidative stress. Additionally, PPLS-1 extended the lifespan of Drosophila melanogaster. Quantitative real-time PCR (qRT-PCR) results indicated that this lifespan extension was associated with upregulation of Nrf2 and HO-1 mRNA levels. These findings provide a foundation for further research on P. pubescens and support the potential development of its polysaccharides as antioxidant and anti-aging agents.